The Therapeutic Relationship in EMDR Therapy - Hase, Michael; Brisch, Karl Heinz (Frontiers in Psychology, 2022)
The history of EMDR Therapy goes back to 1987, when it was introduced as EMD, a novel treatment for PTSD by Francine Shapiro. Over the course of time EMD developed into the comprehensive therapy approach named EMDR Therapy. The development of the ‚Adaptive Information Processing (AIP) Model’, the model of pathogenesis and change of EMDR Therapy, was a milestone in this development from technique to psychotherapy approach. Up to date EMDR Therapy offers not only a model of pathogenesis and change, but also a variety of treatment plans and techniques to treat patients of various diagnosis far beyond PTSD. What seems to be missing is a specific description of the therapeutic relationship in EMDR Therapy. The therapeutic relationship should be described as a core element of EMDR Therapy, and seems be related to the structure of EMDR Therapy. As attachment theory offers a view on the development of interpersonal relationships in general, an attachment theory based perspective of the therapeutic relationship seems advisable. A description of the therapeutic relationship in EMDR Therapy is necessary at this point of the development of EMDR Therapy to a psychotherapeutic approach and therefore we try to describe the therapeutic relationship in this article and point out parallels between the therapeutic relationship and the development and core features of an attachment based relationship. We propose to describe EMDR Therapy as a sensitive psychotherapy. Implications for treatment, training and research will be discussed.